Leadership of the Head of Madrasah in Improving Teacher Performance in MTs Al-I'anah Klari Karawang - Haikal Arya Akbar; Hinggil Permana (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2022)
The school headmaster is one of the factors in encouraging the school to reach its vision, mission, aim and target through the planned and implemented program. The aim of the study is to know the leadership of the headmaster of the school in improving the teachers’ commitment, work motivation, and obstacles experienced by the school headmaster in improving the teachers’ performance at MTs Al-I'anah. The study used the descriptive method. The data collection techniques were observations, interviews, and documentation. The subjects of this research were the headmaster of the school and the teachers of MTs Al-I'anah. The data analysis of this qualitative analysis shows that: (1) The leadership of the headmaster of the school in improving working commitment is thought empowerment of the training teacher in accordance with their field, class supervision evaluation and interns routinely madrasah supervision, and give reward to outstanding teacher; (2) The school headmaster leadership in improving work motivation is through professionalism work guiding, evaluate the teacher learning program, consensus agreement in time discipline, and intern cooperation with thie school headmaster and guiding teachers; (3) The headmaster leadership in improving discipline is through applying self discipline of school headmaster in order to be followed by teachers as the discipline being conducted by the school headmaster in fully self awareness without any coercion; (4) The obstacles faced by the school headmaster in improving the teacher performance is because of time restriction in carrying out classroom supervision, guiding professional teachers and evaluate the teachers teaching-learning process, as well as restricted fund allocation in MTs Al-I'anah.